Accuracy and Systematic Biases of Heart Rate Measurements by Consumer-Grade Fitness Trackers in Postoperative Patients: Prospective Clinical Trial - Philipp Helmer; Sebastian Hottenrott; Philipp Rodemers; Robert Leppich; Maja Helwich; Rüdiger Pryss; Peter Kranke; Patrick Meybohm; Bernd E Winkler; Michael Sammeth (JMIR Publications, 2022)
BackgroundOver the recent years, technological advances of wrist-worn fitness trackers heralded a new era in the continuous monitoring of vital signs. So far, these devices have primarily been used for sports. ObjectiveHowever, for using these technologies in health care, further validations of the measurement accuracy in hospitalized patients are essential but lacking to date. MethodsWe conducted a prospective validation study with 201 patients after moderate to major surgery in a controlled setting to benchmark the accuracy of heart rate measurements in 4 consumer-grade fitness trackers (Apple Watch 7, Garmin Fenix 6 Pro, Withings ScanWatch, and Fitbit Sense) against the clinical gold standard (electrocardiography). ResultsAll devices exhibited high correlation (r≥0.95; P<.001) and concordance (rc≥0.94) coefficients, with a relative error as low as mean absolute percentage error <5% based on 1630 valid measurements. We identified confounders significantly biasing the measurement accuracy, although not at clinically relevant levels (mean absolute error<5 beats per minute). ConclusionsConsumer-grade fitness trackers appear promising in hospitalized patients for monitoring heart rate. Trial RegistrationClinicalTrials.gov NCT05418881; https://www.clinicaltrials.gov/ct2/show/NCT05418881